STATISTICAL EVALUATION OF THE EFFECTIVENESS CREDIT UNIONS' ACTIVITIES BY REGIONS - O. Ivanenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
According to the research results efficiency of the credit unions management is assesed on the basis of the indices analysis, which characterize the effect of the credit union activities and compliance of the functioning this non-commercial organization with the purposes of its statutory activity.